Pengaruh Intensitas Research & Development dan Ownership Retention Terhadap Intellectual Capital Disclosure Pada Perusahaan Yang Melakukan IPO Di BEI - Kurniawati, Usi; Suharti, Sri (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2023)
Intellectual capital disclosure is referred to as a effort made to communicate financial reports by presenting various business activities that are reliable, integrated, correct and fair. This study intends to ascertain the impact of research & development intensity, and ownership retention on intellectual capital disclosure that conducts initial public offering of companies. Quantitative information was based on secondary data from the Indonesian Stock Exchange. Data analysis techniques using SPSS. This study shows that the research & development intensity variable has no effect on intellectual capital disclosure. While disclosure of intellectual capital is significantly influenced by ownership retention variables. This is because investors tend to be attracted to companies that disclose their intellectual capital in full. The purpose of disclosing intellectual capital can only be achieved through the principle of transparent information (good corporate governance) so that investors have confidence in stakeholders.